Business the AOL way : secrets of the world's most successful Web company - Stauffer, David. (Capstone, 2000)
AOL is the world's single most successful Internet-based company, whether measured by number of customers, annual revenues, or profits. CEO Steve Case is a visionary, a charismatic leader who has taken AOL from obscurity to become the pre-eminent new-media brand in less than 10 years.